Study on the structure and properties of fine-grained alumina fast sintered with high heating rate - Meng, F; Fu, Z; Zhang, J; Wang, H; Wang, W; Wang, Y; Todd, R; Zhang, Q (2008)
Fine-grained alumina was obtained in 2 min by a new densification method based on Self-propagating High-temperature Synthesis plus Quick Pressing (SHS/QP). The sample was densified to more than 99% of theoretical density under a large mechanical pressure (100 MP) and a fast heating rate (1600 °C/min). Compared with the alumina sample obtained by spark plasma sintering (SPS) at lower heating rates (100 or 500 °C/min), almost no grain growth was found in the sample obtained in this work. The microstructure and mechanical properties were studied. Hardness value of 18.6 ± 0.4 GPa and fracture resistance value of 3.4 ± 0.3 MPa m1/2 were measured for fine-grained alumina of this work. The densification mechanism was discussed. © 2008 Elsevier Ltd. All rights reserved.